Reinforcement corrosion in limestone flash calcined clay cement-based concrete. (June 2020) - Nguyen, Quang Dieu; Castel, Arnaud
Abstract: Limestone calcined clay cement (LC3) concrete has attracted world-wide attention as a newly promising low-carbon concrete. In this study, long-term reinforcement corrosion in LC3 concrete was investigated. Both chloride and carbonation-induced reinforcing bar corrosion were examined. Open circuit corrosion potential, polarization resistance, Tafel constants were monitored at regular intervals up to 500 days. Gravimetric mass loss was measured and compared to the loss of mass calculated using electrochemical methods. The performance of concrete with flash calcined clay and limestone was similar to that of traditional Portland cement concrete in long-term investigation. Traditional corrosion methods and classifications used widely to assess of steel in concrete can be applied to concrete containing LC3 providing a recalibration of polarization resistance range for passitivity condition.